(untitled) (Bioscience Journal, 2015)
The optimization of growth conditions for the production of inulinase by Penicillium funiculosum cells were studied as well as the continuous production of the enzyme using immobilized cells. The highest amount of enzyme (163.5U/mL) was obtained when the producing cells were incubated for 96 hours at 27oC and 200 rpm in a fermentation medium containing both inulin and peptone as sole carbon and nitrogen sources respectively. However, when the cells of the tested microorganism were adsorbed on different carriers, especially linen fibers, their production ability was also successfully maintained, to different extends, for seven successive batches. Moreover, commercially pure inulin is very expensive in only small quantities, this fermentation medium was later substituted by a crude inulin solution obtained from Jerusalem artichoke tubers (Helianthus tuberosus). The crude inulin juice was able to sustain inulinase production during the second batch cultivation of the P. funiculosum, immobilized by their adsorption on linen fibers, in a satisfactory level of about 122U/mL. Moreover, the use of the previously mentioned crude inulin preparation was also compared to the use of either complete or minimal media, composed solely of 1% pure inulin. The method, adopted in this study for inulinase production, is simple, economic, time saving, non-toxic to the microorganism and the loaded linen pads are reusable.